2020
DOI: 10.1016/j.jaad.2020.06.1016
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of COVID-19–associated dermatologic manifestations: An international registry of 716 patients from 31 countries

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
550
6
44

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(625 citation statements)
references
References 30 publications
(53 reference statements)
25
550
6
44
Order By: Relevance
“… 17 Morbilliform, urticarial, pseudochilblain, vesicular, papulosquamous, pernio-like, livedoid, and necrotic lesions have all been described in large case series and systematic reviews. 16 , 17 , 18 , 19 Pediatric patients with COVID-19 who do not have MIS-C have been described as having similar eruptions as adults, such as acral chilblain-like 20 , 21 , generalized papulovesicular, maculopapular, and morbilliform eruptions. 17 Cutaneous findings specific to MIS-C, however, are not as well outlined in the current literature.…”
Section: Dermatologic Presentationmentioning
confidence: 99%
“… 17 Morbilliform, urticarial, pseudochilblain, vesicular, papulosquamous, pernio-like, livedoid, and necrotic lesions have all been described in large case series and systematic reviews. 16 , 17 , 18 , 19 Pediatric patients with COVID-19 who do not have MIS-C have been described as having similar eruptions as adults, such as acral chilblain-like 20 , 21 , generalized papulovesicular, maculopapular, and morbilliform eruptions. 17 Cutaneous findings specific to MIS-C, however, are not as well outlined in the current literature.…”
Section: Dermatologic Presentationmentioning
confidence: 99%
“…The most common reported dermatologic presentations in confirmed or highly suspected patients are morbilliform, pernio-like, urticaria, macular erythema, vesicular, papulosquamous and retiform purpura. ( Freeman et al, 2020 ) We had limitation of antiganglioside antibody testing to identify a specific target of autoimmune process and also SARS-Cov-2 PCR on CSF, but it has been reported negative in all the other published cases ( Caress et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, considerable research has been focused on the virus’ rash-related symptoms, and a variety of skin lesions associated with COVID-19 have been described [ 14 19 ]. Recently, findings of an international registry from 31 countries, collecting 716 cases of new-onset cutaneous manifestations in patients with confirmed or suspected COVID-19, were published.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, findings of an international registry from 31 countries, collecting 716 cases of new-onset cutaneous manifestations in patients with confirmed or suspected COVID-19, were published. Authors described the following skin lesions in patients with confirmed COVID-19: morbilliform (22%), pernio-like (18%), urticarial (16%), macular erythema (13%), vesicular (11%), papular-squamous (9.9%), and retiform purpura (6.4%) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation